2016
DOI: 10.1186/s13046-016-0462-4
|View full text |Cite
|
Sign up to set email alerts
|

Patient-derived xenografts: a relevant preclinical model for drug development

Abstract: Identifying appropriate preclinical cancer models remains a major challenge in increasing the efficiency of drug development. A potential strategy to improve patient outcomes could be selecting the ‘right’ treatment in preclinical studies performed in patient-derived xenografts (PDXs) obtained by direct implants of surgically resected tumours in mice. These models maintain morphological similarities and recapitulate molecular profiling of the original tumours, thus representing a useful tool in evaluating anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 41 publications
2
114
0
1
Order By: Relevance
“…As anticipated, we found that cancer cells purified from BALB/c tumors expressed very high levels of cytokines, growth factors and members of the INFα/β and INFγ signaling pathways, hallmarks of an active interaction with the immune system. While PDX mice will continue to be invaluable resources for exploring therapeutic treatments that are independent of immune function, such as chemotherapies and cell cycle checkpoint inhibitors [33], therapies that engage the immune system to kill the tumor will require the development of ex vivo bioreactor type methodologies that will permit the incorporation of all immune components.…”
Section: Discussionmentioning
confidence: 99%
“…As anticipated, we found that cancer cells purified from BALB/c tumors expressed very high levels of cytokines, growth factors and members of the INFα/β and INFγ signaling pathways, hallmarks of an active interaction with the immune system. While PDX mice will continue to be invaluable resources for exploring therapeutic treatments that are independent of immune function, such as chemotherapies and cell cycle checkpoint inhibitors [33], therapies that engage the immune system to kill the tumor will require the development of ex vivo bioreactor type methodologies that will permit the incorporation of all immune components.…”
Section: Discussionmentioning
confidence: 99%
“…Although thousands of genomic profiles of patient tumors are available, accurate information about pharmacological interventions and treatment outcome has not been systematically collected [23], or has not been disclosed yet [24]. Thus, to bypass these limitations, we compiled drug response data obtained in PDXs, since they preserve the overall molecular profile of the original tumor, and maintain its cellular and histological structure [32]. In particular, we based our study on 375 PDXs for which somatic mutations and copy number alterations have been characterized, together with their response to 62 treatments across six indications, using the 'one animal per model per treatment (1x1x1)' experimental design [28].…”
Section: Driver Co-occurrence Network Of Drug Responsementioning
confidence: 99%
“…To some extent, PDXs preserve inter-and intra-tumoral heterogeneity, and mimic the clinical course of the disease and response to targeted therapy, at least in certain tumor types [29][30][31]. Indeed, a recent review reported a 91% (153 out of 167) correspondence between the clinical responses of patients and their cognate PDXs [32]. Although this data are more time-intensive and expensive to generate, it is still feasible to establish large in vivo screenings, covering a wide diversity of tumor types and drugs.…”
Section: Introductionmentioning
confidence: 99%
“…7 Tumors are maintained by passaging fragments directly from mouse to mouse and then expanded for the evaluation of anticancer efficacy of treatments. Usually the time for engraftment is between 2 and 4 months and failure of engraftment should not be ascertained until at least 6 months and beyond.…”
Section: Patient Derived Xenograftsmentioning
confidence: 99%